2008
DOI: 10.1166/jnn.2008.092
|View full text |Cite
|
Sign up to set email alerts
|

Scratch and Wear Resistance of Polyamide 6 Reinforced with Multiwall Carbon Nanotubes

Abstract: While carbon nanotubes have been used for a variety of purposes, it was not known whether they can improve tribological properties of polymers. Polyamide 6 (PA6) has been reinforced with 0.2, 0.5 and 1.0 wt% of multiwall carbon nanotubes (MWCNTs) by melt mixing process and characterized by scanning electron microscopy (SEM), transmission electron microscopy, thermogravimetric analysis (TGA), scratching, sliding wear and tensile testing. TGA results for the air atmosphere show that MWCNTs shift the onset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Giraldo et al [41] observed for PA6/MWCNTs nanocomposites the onset shift of thermal degradation to higher temperatures with increase of scratch hardness while avoiding the damage on the surface, without the presence of any debris in broad range of applied loads.…”
Section: Resultsmentioning
confidence: 99%
“…Giraldo et al [41] observed for PA6/MWCNTs nanocomposites the onset shift of thermal degradation to higher temperatures with increase of scratch hardness while avoiding the damage on the surface, without the presence of any debris in broad range of applied loads.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of small quantities of CNTs into a polymer matrix can lead to obtain structural composites with high elastic modulus, high tensile and compressive strength and stiffness. The mechanical properties combined with electrical, thermal, optical and many other properties have been extensively investigated by many research groups for wide range of applications [22][23][24][25][26][27][28][29][30]. In this work, poly(trimethylene terephthalate)/multiwalled carbon nanotubes nanocomposites were prepared by in situ polymerization method.…”
mentioning
confidence: 99%
“…Specimens were tested using a CSM Micro-Scratch Tester (MST) following the procedure previously described [1,2,6,[15][16][17]. Sliding wear (repetitive scratching along the same groove) tests were performed as follows: normal load 5.0, 10.0 and 15.0 N; scratch length 5.0 mm; scratch velocity 2.5, 5.0 and 15.0 mm/min at room temperature.…”
Section: Scratch Testingmentioning
confidence: 99%
“…Thus, for epoxy + silica nanohybrids there is an improvement of both mechanical and tribological properties [1]. By contrast, for Polyamide 6 reinforced with multiwall carbon nanotubes (MWCNTs) there is an improvement of mechanical properties; however, scratch recovery is hampered by the presence of CNTs [2] while the scratch depths can be either shallower or deeper, depending on the CNTs diameter and also on functionalization. Thus, creation of polymer-based nanohybrids seems be a two-edged sword.…”
Section: Introductionmentioning
confidence: 99%